Private security contractors and new wars risk, law, and ethics - Carmola, Kateri (Contemporary security studies, 2010)
This book addresses the ambiguities of the growing use of private security contractors and provides guidance as to how our expectations about regulating this expanding 'service' industry will have to be adjusted. In the warzones of Iraq and Afghanistan many of those who carry weapons are not legally combatants, nor are they protected civilians. They are contracted by governments, businesses, and NGOs to provide armed security. Often mistaken as members of armed forces, they are instead part of a new protean proxy force that works alongside the military in a multitude of shifting roles, and overseen by a matrix of contracts and regulations. This book analyzes the growing industry of these private military and security companies (PMSCs) used in warzones and other high risk areas. PMSCs are the result of a unique combination of circumstances, including a change in the idea of soldiering, insurance industry analyses that require security contractors, and a need for governments to distance themselves from potentially criminal conduct. The book argues that PMSCs are a unique type of organization, combining attributes from worlds of the military, business, and humanitarian organizations. This makes them particularly resistant to oversight. The legal status of these companies and those they employ is also hard to ascertain, which weakens the multiple regulatory tools available. PMSCs also fall between the cracks in ethical debates about their use, seeming to be both justifiable and objectionable. This transformation in military operations is a seemingly irreversible product of more general changes in the relationship between the individual citizen and the state. This book will be of much interest to students of private security companies, war and conflict studies, security studies and IR in general.